Nowy/obcy w szkole – jaki obraz ucznia cudzoziemskiego przedstawiają nauczyciele szkół podstawowych (wnioski z badania ankietowego) - Różycka, Natalia (Slavia Occidentalis, 2024)
This article is a development of a paper delivered during the Forum Młodych Badaczy Języka Regionu (Forum for Young Language Researchers of the Region) organized on 3 March 2022 by the Studenckie Dialektologiczne Koło Naukowe (Students’ Dialectology Study Group) that took place at the Faculty of Polish and Classical Philology of Adam Mickiewicz University in Poznań. The aim of this text is to show how primary school teachers perceive foreign students in Polish primary schools. The overriding issue is the teachers’ opinions on the communication barrier and if the perceived difficulties spearhead measures to minimize the difficulties by, among other things, enhancing (glotto)didactic competences. The considerations are based on the findings of a survey conducted by the author in 2021 as part of her bachelor’s thesis. The analysis and interpretation include statements of teachers of the second stage of education. With the help of tools developed within the framework of cognitive methodology (linguistic worldview), profiles of foreign students have been identified. The material shows how teachers perceive and value foreign learners and which teaching aids they can use while educating this group of pupils.